EVALUASI PERTUMBUHAN BENIH IKAN MAS (Cyprinus carpio) YANG DIBERI PAKAN TAMBAHAN PERIFITON - Suardi Laheng; Dwi Utami Putri; Rifaldi Rifaldi (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
The purpose of this study was to determine the growth of Cyprinus carpio seeds fed with additional periphyton feed. This research was conducted for 2 months in Tambun Village, Tolitoli Regency, Central Sulawesi. The treatments tested were P1 = Without periphyton (Control), P2 = Substitution of periphyton every 3 days, P3 = Substitution of periphyton every 5 days, P4 = Substitution of periphyton every 7 days. The results showed that the administration of periphyton to Cyprinus carpio had no effect on growth.